An analysis of the non-convecting solar pond - Hawlader, Mohammad Nurul Alam; Brinkworth, B J (Pergamon Press Ltd., 1981)
The thermal behaviour of the non-convecting solar pond is examined by numerical solution of the dynamic equations, incorporating detailed representation of the losses from the surface and using hourly meteorological data for a site in southern England. Temperature histories for the first few years of operation are given, showing the influence of the leading physical characteristics of the pond. It is shown that the pond temperatures are strongly dependent on the effective extinction coefficient for solar radiation and the thermal losses from the pond bottom. The temperature history approaches a quasi-steady form within two to three years of operation, depending on the load demand. Using realistic assumptions for the main determinants of pond behaviour, it is shown that modest loads (around 10 per cent of the average insolation) can be served in this climate at temperatures appropriate for practical applications